THE IMPORTANCE OF MANAGEMENT INDEPENDENCE IN SUPPORTING THE DEVELOPMENT OF SCIENCE, EDUCATION, RESEARCH AND INNOVATION IN HIGHER EDUCATION INSTITUTIONS (Scientific Journal of Actuarial Finance and Accounting, 2024)
This paper dives into how science and education are like the heartbeat of society, constantly pulsing with new energy from the younger generation. It's like a dance between fresh perspectives and timeless wisdom, all aimed at pushing us forward. We explore how governments are like the scaffolding, supporting the growth of education and scientific research, laying the groundwork for progress. But it's not just about building at home; we also look abroad, borrowing moves from others in the global dance of education. We chat about different flavors of quality control in universities worldwide, recognizing that each brings its own spice to the mix. And we don't forget the real reason we're all here: to prepare folks for the dance of the job market, making sure our education isn't just theory but practical too. Ultimately, it's about creating a harmony between education, science and society, ensuring that together we can waltz into a brighter future.